Control of Japanese stiltgrass (Microstegium vimineum) in golf course natural areas. (20th October 2020) - Weaver, Josh R.; Brown, Philip J.; McCarty, Lambert B.; Gambrell, Nathaniel
Abstract: Japanese stiltgrass is regarded as one of the most troublesome invasive species in the United States. It is commonly found invading forested areas; however, more recently it has been noted to be invading golf course roughs and out-of-play areas. The purpose of this study was to evaluate POST herbicide control of Japanese stiltgrass in golf course and highly maintained turfgrass facilities. None of the treatments provided >80% Japanese stiltgrass control 2 wk after treatment (WAT). At 4 WAT >80% Japanese stiltgrass control was observed with MSMA, MSMA + metribuzin, amicarbazone, and sethoxydim, whereas metsulfuron, pinoxaden, and imazapic provided minimum control. By 8 WAT, MSMA, MSMA + metribuzin, amicarbazone, and sethoxydim provided >98% control, whereas quinclorac, metsulfuron, pinoxaden, and imazapic provided no visible control. Thiencarbazone-methyl + foramsulfuron + halosulfuron-methyl, and sulfentrazone provided limited (≤60%) control. This study indicates that POST control of Japanese stiltgrass can be achieved with MSMA, MSMA + metribuzin, amicarbazone, and sethoxydim. Future research should include long-term control over multiple growing seasons, repeat applications of herbicides, and evaluation of herbicides in combination for increased and longer-term Japanese stiltgrass control.